STUDI KASUS RHEUMATOID ARTHRITIS DENGAN MASALAH KEPERAWATAN GANGGUAN MOBILITAS FISIK - Putri, Yulia Devi; Yona Febrina, Trisya; Aglusi Badri, Isna; Santi, Santi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Objective: To identify Rheumatoid Arthritis Problems with Physical Mobility Disorders nursing problemsMethods: . This study is a descriptive study using a case study design. Data collection using interview techniques, observation and providing nursing actions and conducting nursing evaluations.Results: The results obtained increased range of motion marked by the patient being able to move without interference. The nursing diagnosis found was Impaired Physical Mobility related to Joint Stiffness. The problem can be resolved on the third day of nursing implementation.Conclusion: It is hoped that this research can improve nursing care for Rheumatoid Arthritis clients from determining the diagnosis to nursing evaluation, can improve the quality of service to be better, as a reference material in the development of science, and respondents with impaired physical mobility can mobilize well.. Keywords: Nursing Care, Rheumatoid Arthritis, Physical Mobility Impairment.